Barriers to Palliative Care Referral and Advance Care Planning (ACP) for Patients With COPD: A Cross-Sectional Survey of Palliative Care Nurses. (February 2022) - Disler, Rebecca; Pascoe, Amy; Luckett, Tim; Donesky, Doranne; Irving, Louis; Currow, David C.; Smallwood, Natasha
Background: Chronic obstructive pulmonary disease (COPD) is a progressive, life-limiting illness that requires end-of-life care planning, yet remains under-served. Understanding barriers to advance care planning (ACP) from different specialties' perspectives will enable a co-ordinated, cross-disciplinary approach to improving ACP access. Methods: Australia and New Zealand palliative care nurses were invited to complete an anonymous online cross-sectional survey. Questions tested knowledge of validated ACP-related practice indicators and canvassed perspectives on barriers to ACP in COPD. Data are described and free-text thematically analyzed. Results: The 90 participants had high knowledge and positive attitudes to ACP in COPD, however, lacked consensus as to whether patients want to know their prognosis or discuss treatment options and end-of-life wishes. 59% discussed ACP in more than half their patients with COPD, and 77% and 73% routinely initiated or followed-up these discussions. Key barriers included: lack of confidence and training in COPD; reluctance to distress patients and families; referral late in the disease course; lack of consensus on referral timing; and lack of patient and clinician understanding of COPD prognoses. Many reported that lack of consensus in the treating team, paired with prognostic uncertainty, precluded timely ACP engagement. Conclusions: Palliative care nurses have substantial knowledge and positive beliefs regarding ACP, however, some beliefs and practices lack alignment with qualitative data on patients' wishes in COPD. While palliative care nurses are well placed to facilitate early implementation for patients with advanced COPD, ACP training and practice guidelines specific to COPD may increase implementation in this life-limiting disease.